Incidence of Listeria spp. and Listeria monocytogenes in a poultry processing environment and in poultry products and their rapid confirmation by multiplex PCR. - Lawrence, L M (1994)
The incidence of Listeria spp. and Listeria monocytogenes in a poultry processing plant and in raw and cooked poultry products was determined over a 6-month period. Within the raw and cooked poultry processing environments, 46% (36 of 79) and 29% (51 of 173) of the samples contained Listeria spp. while 26% (21 of 79) and 15% (27 of 173) contained L. monocytogenes, respectively. Various sites within the processing environment were found to be consistently positive for L. monocytogenes throughout the entire sampling period. Of the raw and cooked products tested, 91% (53 of 58) and 8% (8 of 96) were found to contain Listeria spp. while 59% (34 of 58) and 0% (0 of 96) contained L. monocytogenes, respectively. Although L. monocytogenes was not detected in the cooked products examined, the presence of other Listeria spp. highlights the potential which exists for postprocessing contamination. Multiplex PCR proved to be a convenient and time-saving technique for rapid confirmation of Listeria spp. and L. monocytogenes in a single reaction.